Patient’s knowledge, attitude regarding dental implants in Qassim, SaudiArabia - Abdulrahman Alajlan; Aryaf Alhoumaidan; Abeer Ettesh (Saudi Dental Journal)
Aim: The purpose of this survey was to evaluate the level of knowledge, attitude and source of information regarding use dental implant as treatment option compared to other conventional treatment modalities. Materials and methods: A descriptive cross sectional study among adult dental patients attended Qassim university dental clinics of college of dentistry. The level of knowledge, source of information & attitude regarding use dental implant were evaluated through standardized self- explanatory questionnaires which were handed to the patient during their regular dental visits. 200 patient were selected randomly to be included in this survey. Results: Among 200 respondents in this study, 91.5% of respondents heard about implants and their source of information were friends (45.5%), 38% of respondents had no idea about the oral hygiene for the care of the implants compared with natural teeth, 28.5% of respondents expected them to last between 10 and 20 years, 48.5% of the respondents believed that dental implants have no effect on the systemic health. There is significant difference between males & females. Conclusion: The survey concluded that an acceptable level of awareness regarding using dental implants as a treatment option for replacing missing teeth, with Friends being the main source of information.